Proximate determinant of fertility in India and estimation of total fertility rate - Tiwari, Abhay Kumar; Maurya, Ravi Kant; Singh, Pappu Kumar (Brazilian Journal of Biometrics, 2025)
Fertility is one of the crucial components in the study of population changes. In India, Total Fertility Rate (TFR) has declined steadily as observed by National Family Health Survey (NFHS) from 1991-92 (2.7) to 2019-21 (2.0) child per women. There is large variation in fertility due to fact that variations in geographic, environmental, behavioural and social factors. To measure the fertility, Bongaart’s (1982) proposed a model to estimate TFR using four specific factors (Marriage, Contraception, Induced abortion and Lactational infecundability). In this article, we have estimated the indices of the proximate determinants of fertility for India and using these indices, we have estimated the total fertility rate for 2019-21 of India and its major states. There were large differences found in the observed and estimated values of TFR for India as well as its states. So, we try to investigate whether this model with some modification may provide reasonable estimates of TFR? For estimation of Lactational infecundability Index, we have calculated postpartum amenorrhea (PPA) using Prevalence/ Incidence method. The studies indicate that contraception (66.7%) had the most significant impact on reducing fertility rates in India followed by marriage (36.4%), lactational infecundability (20.6%) and induced abortion (1%).